2022
DOI: 10.1038/s41416-022-02021-z
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations are associated with pathologic complete response rate to neoadjuvant pyrotinib and trastuzumab plus chemotherapy for HER2-positive breast cancer

Abstract: Background Neoadjuvant treatment with a dual anti-human epidermal growth factor receptor 2 (HER2) blockade with pyrotinib and trastuzumab has been shown to be effective for HER2-positive breast cancer. Methods The genomic characteristics of 425 cancer-related genes from the archived tumour blocks of 50 patients enrolled in a prospective neoadjuvant pyrotinib and trastuzumab plus chemotherapy clinical trial (ChiCTR1900022293) were assessed by next-generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
(62 reference statements)
2
14
1
Order By: Relevance
“…[32][33][34] In addition, we previously reported a significant relationship between PIK3CA mutations and lower pCR rate (adjusted p= 0.024) among 425 cancer-related genes assessed by next-generation sequencing of archived tumor blocks from 50 patients enrolled in this clinical trial. 35 This finding is consistent with some previous reports. However, the result was puzzlingly opposite to the findings of NeoATP trial, which reported no statistically significant difference in terms of pCR between subgroups by PIK3CA status (p = 0.958).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…[32][33][34] In addition, we previously reported a significant relationship between PIK3CA mutations and lower pCR rate (adjusted p= 0.024) among 425 cancer-related genes assessed by next-generation sequencing of archived tumor blocks from 50 patients enrolled in this clinical trial. 35 This finding is consistent with some previous reports. However, the result was puzzlingly opposite to the findings of NeoATP trial, which reported no statistically significant difference in terms of pCR between subgroups by PIK3CA status (p = 0.958).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, we previously reported a significant relationship between PIK3CA mutations and lower pCR rate (adjusted p = 0.024) among 425 cancer‐related genes assessed by next‐generation sequencing of archived tumor blocks from 50 patients enrolled in this clinical trial 35 . This finding is consistent with some previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…We assessed 425 genes in tumor samples from patients receiving neoadjuvant therapy with pyrotinib, trastuzumab, and chemotherapy. We concluded that the PIK3CA mutation was an independent predictor of therapeutic effects; patients with a PIK3CA mutation were less likely to achieve pCR, whereas the TIL level was not associated with pCR [ 85 ]. Those biomarker studies could preliminarily guide the selection of patients more likely to benefit from pyrotinib-based regimens.…”
Section: Clinical Evidence Of Pyrotinib In Early Bcmentioning
confidence: 99%
“…In addition, TP53, PIK3CA, and other genetic mutations were reported to affect the efficacy of targeted therapy and prognosis of patients with HER2‐positive BC 9 . It has been reported that HER2‐positive breast cancers with activating mutations in PIK3CA are less likely to benefit from NAT 10,11 . Chemotherapy and radiotherapy cause DNA damage in tumor cells, and TP53 induces apoptosis after DNA damage 12 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 It has been reported that HER2‐positive breast cancers with activating mutations in PIK3CA are less likely to benefit from NAT. 10 , 11 Chemotherapy and radiotherapy cause DNA damage in tumor cells, and TP53 induces apoptosis after DNA damage. 12 Many studies have proven that TP53 mutation can increase the pCR rate of neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%